Nicotine and Cognition in Cognitively Normal Older Adults - Nop, Olivia; Senft Miller, Anna; Culver, Hannah; Makarewicz, Jenna; Dumas, Julie A. (Frontiers in Aging Neuroscience, 2021)
The cholinergic system has been shown to be the primary neurotransmitter system responsible for the cognitive symptoms associated with dementia; its role in healthy non-demented older adults remains a gap in the literature. Understanding the effects of age-related functional changes on the nicotinic system will address this knowledge gap. As the older adult population grows, so does the importance of understanding cognitive changes that impact functional abilities in normal aging and perhaps everyday life. In this paper we will examine the benefits of using nicotine as a method for slowing neurodegeneration in healthy, non-demented individuals. Furthermore, we will discuss how nicotine can play a crucial role in maintaining cognitive abilities throughout non-pathological aging.